Assessment of Air Quality and Noise around Okrika Communities, Rivers State, Nigeria - AE Gobo; TJK Ideriah; TE Francis; HO Stanley (Journal of Applied Sciences and Environmental Management)
The quality of air and noise levels around Okirika communities in River State were determined using portable hand held air monitors for air pollutants and anemometer for meteorological parameters. The parameters measured were suspended particulate matter, nitrogen dioxide, sulphur dioxide, hydrogen sulphide, ammonia, carbon monoxide, methane and volatile organic carbon, temperature, wind speed, wind direction and relative humidity. The results showed the highest concentrations of 0.007mg/m3 (PM1, dry), 0.036mg/m3 (PM2.5, dry), 0.286mg/m3 (PM7, dry), 0.378mg/m3 (PM10, dry), 0.503mg/m3 (TSP, dry), 1.7ppm (NO2, dry), 3.0ppm (CH4, dry), 0.2ppm (H2S, dry), 12.7ppm (CO, dry), 2.7ppm (NH3, dry), and 7.0ppm (VOC, rainy). The dry season concentrations of air pollutants were higher than the rainy season concentrations. The observed differences in mean concentrations of the air pollutants between the two seasons were not significant in case of TSP (P<0.05) but were significant (P<0.05) in other pollutants. The highest mean concentrations of the gaseous pollutants exceeded permissible limits and therefore pose environmental and health concern for the inhabitants of the area. The quality of air in the area is poor and need to be regularly monitored. @JASEM